Has Foreign Aid Improved Health Outcomes in Uganda? Evidence from Panel Microdata - Odokonyero, Tonny; Marty, Robert (Economic Policy Research Centre, 2017)
The health sector has attracted significant foreign aid; however, evidence on the effectiveness of this support is mixed. We combine household panel data with geographically referenced foreign aid data and use a quasi-experimental approach to investigate the contribution of aid on key health outcomes in Uganda. We find that overall, health aid achieved a significant impact on reducing both disease severity and burden—with the largest impact on disease burden. In addition, we observe aid is more effective if resources are channelled to locations and facilities that are closer to communities in need, given the ease of access to health services. From a policy perspective, aid ought to be channelled as close to intended beneficiaries as possible, thus advancing the Universal Health Coverage strategy of “close to client” health system.